Recent Advances on Metalloporphyrin‐Based Materials for Visible‐Light‐Driven CO2 Reduction. Issue 23 (21st September 2020) - Zou, Lei; Sa, Rongjian; Lv, Haowei; Zhong, Hong; Wang, Ruihu
Abstract: Photocatalytic CO2 reduction is a promising technology to mitigate environmental issue and the energy crisis. The four nitrogen atoms in the porphyrin ring can incorporate transition metals to form stable active sites for CO2 activation and photoreduction. Nevertheless, the photocatalytic efficiency of metalloporphyrins is still low due to the insufficient photoelectron injection to drive CO2 photoreduction upon visible light irradiation. To address this issue, considerable efforts have been made to introduce photosensitizers for constructing homogeneous or heterogeneous metalloporphyrin‐based photocatalytic systems. In this Review, recent advances of metalloporphyrin‐based materials for visible‐light‐driven CO2 reduction were summarized. The methods for the modulation of photosensitizing process at molecular level were presented for the promotion of photocatalytic performance. The mechanism of CO2 activation and photocatalytic conversion was illustrated. Better insight into the structure‐activity relationship provides guidance to the design of metalloporphyrin‐related photocatalytic systems. Abstract : Metalloporphyrin for the win : Metalloporphyrin is an appealing unit for CO2 activation and photocatalytic conversion. The application of metalloporphyrin‐based materials for visible‐light‐driven CO2 reduction are summarized. The protocols for the integration with photosensitizers are demonstrated. The well‐defined structure of the metalloporphyrin unit provides an ideal platform for getting insight into structure‐activity relationships at molecule level.